Transforming biomass into engineered biochar materials for high-performance supercapacitors: Recent advances, challenges, and prospects - Ruibo FAN; Liang CHEN; Beichen XUE; Ao WANG; Yinhai SU; Huiyan ZHANG; Xiangzhou YUAN (能源环境保护)
Supercapacitors are widely considered as advanced energy storage devices with vast development prospects due to their excellent properties, including high specific energy and good cyclic stability. Recently, the development of novel and high-performance supercapacitors has attracted extensive attention. As one of the key components, the electrode material has a significant impact on the electrochemical performance of supercapacitors. Engineering biochar not only has natural advantages such as renewability, cost-effectiveness, and environmental-friendliness but also possesses well-developed properties, including pore structure, functional group, and cyclic stability. Therefore, numerous investigations have been conducted to develop high-performance engineered biochar-based supercapacitors. This review provides an overview of emerging synthesis routes for engineered biochar-based electrode materials and discusses recent advances in various synthesis approaches, offering deeper and more comprehensive information on engineered biochar-based supercapacitors. Machine learning (ML)-based predictions and inverse designs have contributed to the innovation of engineered biochar-based electrode materials for high-performance applications, clarifying the inherent mechanisms and complex relationships between the properties of engineering biochar and the electrochemical performance of supercapacitors. Finally, detailed assessments from perspectives of environmental benefits and economic feasibilities are proposed as science-based guidelines for industries and policymakers. The main existing challenges and solutions of engineered biochar-based energy storage systems are discussed, aiming to accelerate commercial applications of engineered biochar-based supercapacitors.